Measurement of temperature change during the implant site preparation to determine influence of tool characteristics - Bulutsuz, Asli Gunay; Tanyel, Rusutu Cem; Katiboglu, Ahmet Bulent (ELSEVIER SCI LTD, 2016)
Implant site preparation procedure is the most important factor that affects early osseointegration performance of a dental implant. During the side preparation procedure increase in the bone temperature above critic limit causes irreversible osteonecrosis. This heat rise compromises implant area around implants thus ending with unsuccessful osseointegration outcomes. In this experimental study drill tip geometry, drill tip angle and drill sharpness affects on procedure temperature were investigated. Experiments were carried on fresh bovine bones and implant sites were prepared individually for each experimental set. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Temperature measurement; Bone drilling; Drill tip angle; Osteonecrosis; TITANIUM DENTAL IMPLANTS; BONE; PARAMETERS; DESIGN; SPEED; Engineering; Instruments & Instrumentation